2017
DOI: 10.1080/2162402x.2017.1319044
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vaccination with tumor-exosome loaded dendritic cells combined with cytotoxic drug treatment in pancreatic cancer

Abstract: Pancreatic cancer (PaCa) has a dismal prognosis and adjuvant immunotherapy frequently is of low efficacy due to immunosuppressive features of PaCa and PaCa-stroma. We here explored, whether the efficacy of vaccination with tumor-exosome (TEX)-loaded dendritic cells (DC) can be improved by combining with drugs affecting myeloid-derived suppressor cells (MDSC). Experiments were performed with the UNKC6141 PaCa line. UNKC6141 TEX-loaded DC were weekly intravenously injected, mice additionally receiving Gemcitabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 78 publications
2
67
0
Order By: Relevance
“…In the study, autologous DCs were loaded with PaCa cell-derived exosomes to vaccinate for PaCa in xenograft mice together with drugs such as Gemcitabine (GEM), alltransretinoic acid (ATRA) and sunitinib. 128 A reduction of MDSC including tumor-infiltrating MDSC and a decrease in migrating and metastasizing tumor cells was observed in the groups treated with Sun, ATRA and, most efficiently, GEM. Vaccination by DC-TEX with any of the three drugs increased the number of activated T cells in the tumor and subsequently the survival time in mice compared with those vaccinated only by DC-TEX.…”
Section: Anti-metastatic Applicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the study, autologous DCs were loaded with PaCa cell-derived exosomes to vaccinate for PaCa in xenograft mice together with drugs such as Gemcitabine (GEM), alltransretinoic acid (ATRA) and sunitinib. 128 A reduction of MDSC including tumor-infiltrating MDSC and a decrease in migrating and metastasizing tumor cells was observed in the groups treated with Sun, ATRA and, most efficiently, GEM. Vaccination by DC-TEX with any of the three drugs increased the number of activated T cells in the tumor and subsequently the survival time in mice compared with those vaccinated only by DC-TEX.…”
Section: Anti-metastatic Applicationsmentioning
confidence: 89%
“…A reduction in metastatic spread was observed with the combination of (DC-TEX) with sunitinib compared to the group treated with sunitinib alone. 128 The mutant form of the GTPase KRAS is a key driver of PaCa, which controls macropinocytosis in PaCa cells and increases exosome uptake. This led Kamerkar et al to develop exosomes derived from normal fibroblast-like mesenchymal cells to carry siRNA specific to oncogenic KRAS.…”
Section: Anti-metastatic Applicationsmentioning
confidence: 99%
“…These exosomes could be isolated from a patient's biological fluids; bioengineered and transformed to deliver anti-cancer drugs, targeting ligands; and then administered in the form of exosome-based anti-cancer vaccines [77]. In addition, a recent in vivo study has shown that the combination of canonical chemotherapy drugs used for pancreatic cancer treatment (i.e., sunitinib, gemcitabine, and all-trans retinoic acid (ATRA)) with vaccines containing dendritic cells enriched with pancreatic cancer-derived exosomes, significantly inhibits the spread of metastases and extends mice survival thanks to the presence of a higher number of activated T cells in the tumor [78]. Barok M. et al demonstrated, by an in vitro study, that trastuzumab emtansine (T-DM1), an antibody-drug conjugate designed for the specific delivery of cytotoxic drug DM1, a derivative of maytansine, to human epidermal growth factor receptor-2 (HER2)-positive cancer cells, is able to bind to exosomes derived from HER2-positive breast cancer cells and GC cells.…”
Section: Cancer-derived Exosomes As Drug Delivery Vehicles For the Trmentioning
confidence: 99%
“…Furthermore, TEV-pulsed DC were shown to reduce numbers of regulatory T cells (Treg) and augment the therapeutic effect of antibodies against PD-1 and sorafenib in an HCC mouse model [ 118 ]. Therapeutic administration of TEV-loaded DC also showed a beneficial effect alone and in combination with MDSC depletion in pancreatic cancer [ 119 ].…”
Section: Ev In Crosstalk Between Tumor Cells and Dendritic Cellsmentioning
confidence: 99%